High-tech functional polymers designed for applications in organic electronics - Kiriy, Anton; Poetzsch, Robert; Wei, Qiang; Voit, Brigitte (Polymer Degradation and Stability, 2017)
Several examples of polymeric materials specially developed for optoelectronic applications are highlighted demonstrating that by fine-tuning chemistry and architecture in highly aromatic polymers significant progress can be made in their performance. Thus, polymeric semiconductors of controlled architectures and high charge mobility had been prepared. The use of branching allowed to realize highly aromatic polymers of high solubility suitable for solution processing as dielectric materials in OFETs and as light-outcoupling layer of high refractive index in OLEDs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: High refractive index polymers; Hyperbranched polymers; Organic electronics; Polymeric dielectrics; Polymeric semiconductor